Abstract Book 15th Geoparks Conference - Castro, Emanuel (2020)
The UNESCO Global Geoparks (UGGps) are territories of science, education and culture. These develop holistic approaches to sustainable development aiming to create new tools that can reinforce endogenous values and empower local communities. The Estrela Aspiring Geopark was created and implemented based on this reality and principles. Since the beginning, sustainable development of the territory was a priority, considering the uniqueness of the Estrela Mountain area and the importance of the protection and valorisation of its endogenous potential, with emphasis on the geological heritage.